2007
DOI: 10.2337/dc06-1835
|View full text |Cite
|
Sign up to set email alerts
|

Television Viewing Is Associated With Prevalence of Metabolic Syndrome in Hispanic Elders

Abstract: OBJECTIVE -We examined associations between television viewing and prevalence of the metabolic syndrome among a representative sample of Caribbean-origin Hispanic elders living in Massachusetts.RESEARCH DESIGN AND METHODS -We conducted a cross-sectional analysis of 350 Puerto Rican and 105 Dominican elders (Ն60 years). Information on television viewing hours was collected by a questionnaire. The metabolic syndrome was defined by using the definition from the National Cholesterol Education Program.RESULTS -Prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 35 publications
5
78
0
2
Order By: Relevance
“…Four of the seven cross-sectional studies found statistically significant, positive associations between sedentary behavior and metabolic biomarkers. Positive associations were observed with insulin (52), insulin resistance (101,105), and 2-hour glucose (108), but not with fasting plasma glucose (17,84,108) or insulinlike growth factors (109). Inflammation.…”
Section: Biological Pathwaysmentioning
confidence: 96%
“…Four of the seven cross-sectional studies found statistically significant, positive associations between sedentary behavior and metabolic biomarkers. Positive associations were observed with insulin (52), insulin resistance (101,105), and 2-hour glucose (108), but not with fasting plasma glucose (17,84,108) or insulinlike growth factors (109). Inflammation.…”
Section: Biological Pathwaysmentioning
confidence: 96%
“…The second tenet of inactivity physiology is that the various times that people spend sitting or participating in exercise-based leisure-time physical activity are distinct classes of behavior, with distinct determinants (5) and independent effects on risk for disease (19,20,(23)(24)(25)(26). The third, and central, tenet for the paradigm of inactivity physiology is that some of the specific cellular and molecular processes explaining the responses during inactivity physiology versus exercise physiology are qualitatively different from each other.…”
Section: Paradigm Of Inactivity Physiologymentioning
confidence: 99%
“…Metabolic syndrome is a constellation of risk factors for CVD and type 2 diabetes, including plasma triglycerides, HDL cholesterol, plasma glucose, blood pressure, and central adiposity or waist girth. Studies have shown that the classification of people with metabolic syndrome (19,(23)(24)(25) and related metabolic risk factors (31,(35)(36)(37)(38)(39)(40), excessive adiposity or weight gain (5,15,(41)(42)(43)(44)(45)(46), poor glucose management in children with type 1 diabetes (47), and type 2 diabetes risk (20,26,35) have all been directly related to sitting time and/or inversely to low nonexercise activity. Estimations from prolonged TV and computer time led to the conclusion that too much sitting can more than double the risk for metabolic syndrome (19,23,24).…”
Section: A New Concern For Future Public Health Problems?mentioning
confidence: 99%
“…Although several observational studies in seniors have implicated increased sedentary time with elevated risk of having the metabolic syndrome [6,7], most well-conducted studies have focused nearly exclusively on younger individuals. is is despite the fact that seniors are the most sedentary group of all; older adults have been found to reach their exercise targets only 0 to 4.9 percent of the time [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Cross sectional survey based studies have associated less activity with adverse metabolic parameters [6,7]. Because most older adults do not meet current guidelines for physical activity [8], it is di cult to discern whether it is a lack of exercise, excessive sedentary behaviour, or both that leads to metabolic risk.…”
mentioning
confidence: 99%